Implementation of a multidisciplinary infectious diseases team in a tertiary hospital within an Antimicrobial Stewardship Program. Issue 5 (October 2014) - Buyle, F. M.; Wallaert, M.; Beck, N.; Boelens, J.; Callens, S.; Claeys, G.; Deryckere, S.; Haegeman, E.; Leroux-Roels, I.; Sermijn, E.; Steel, E.; Robays, H.; et al.
Abstract : Background: In January 2011, as part of an antimicrobial stewardship program the Antimicrobial Management Team (AMT) at the Ghent University Hospital initiated a multidisciplinary Infectious Diseases Team (MIT) consisting of infectious diseases physicians, clinical microbiologists, and clinical pharmacists. The aim of this study is to describe the type and acceptance rate of recommendations provided by the MIT. Method: Prospective, observational study in a tertiary care, university teaching hospital with 1062 beds in non-consecutive hospitalized adult patients, excluding intensive care units and paediatrics. Results: The MIT communicated 432 recommendations in 87 days observed. Of the 293 patients for whom a recommendation was made, the median age was 57 years (range: 16–91 years) and 169 (57·7%) were male. Skin or soft tissue infections (14%), respiratory tract infections (13%), infections without known focus (11%), abdominal infections (11%), and bone infections (8%) were most common. Recommendations were made to perform additional clinical investigation(s) [ N = 137 (27%)], to adjust the dose of an antimicrobial drug [ N = 42 (8%)], to stop an antimicrobial drug [ N = 104 (21%)], to switch from a parenteral to an oral drug [ N = 39 (8%)] or to initiate an antimicrobial drug [ N = 178 (36%)], with an acceptance rate of 73·0%, 83·3%, 81·7%, 76·9%, and 84·0%, respectively. Conclusions: The MIT formulated about five recommendations a day primarily focusing on pharmacotherapy, but also on clinical investigations. In both fields, a high acceptance rate was observed.